Overview of Health Beliefs of PLWHA Based on the Health Belief Model in Jombang Regency - Soelistijaningsih, Noer; Takariningsih; Widyowati, Agustin (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
HIV/AIDS cases in Indonesia seen in the Asian Epidemic Modeling and Spectrum applications are estimated to be around 543,100 PLWHA spread across Indonesia. Many influences that affect the survival of PLWHA can be seen from the perception of vulnerability, perception of severity, perception of benefits and perception of cues seen in the Health Belief Model theory. The purpose of this study was to determine the health beliefs of PLWHA with the Health Belief Model theory approach. This study used a cross-sectional approach study conducted in Jombang Regency with a population of PLWHA who had access to ARVs and in the scope of the Peer Support Group (KDS JCC Plus) of 666 people. With a sample of 250 obtained. The sampling technique used systematic random sampling. The variables in this study consisted of Independent variables (X1) namely Perception of Vulnerability, X2 namely Perception of Severity, X3 namely Perception of Benefits of action, X4 namely Perception of Barriers, X5 namely perception of Cues to act. With the dependent variable (Y) namely the behavior of PLWHA. It can be concluded that all perceptions have a high average value on question items with contexts related to sexual relations and the use of contraceptives. On average, PLWHA have high confidence in continuing life positively.